Zinc modulation of proton currents in a new voltage‐gated proton channel suggests a mechanism of inhibition. (6th April 2020) - Chaves, Gustavo; Bungert‐Plümke, Stefanie; Franzen, Arne; Mahorivska, Iryna; Musset, Boris
Abstract : The HV 1 voltage‐gated proton (HV 1) channel is a key component of the cellular proton extrusion machinery and is pivotal for charge compensation during the respiratory burst of phagocytes. The best‐described physiological inhibitor of HV 1 is Zn 2+ . Externally applied ZnCl2 drastically reduces proton currents reportedly recorded in Homo sapiens, Rattus norvegicus, Mus musculus, Oryctolagus cuniculus, Rana esculenta, Helix aspersa, Ciona intestinalis, Coccolithus pelagicus, Emiliania huxleyi, Danio rerio, Helisoma trivolvis, and Lingulodinium polyedrum, but with considerable species variability. Here, we report the effects of Zn 2+ and Cd 2+ on HV 1 from Nicoletia phytophila, NpHV 1. We introduced mutations at potential Zn 2+ coordination sites and measured Zn 2+ inhibition in different extracellular pH, with Zn 2+ concentrations up to 1000 μm . Zn 2+ inhibition in NpHV 1 was quantified by the slowing of the activation time constant and a positive shift of the conductance–voltage curve. Replacing aspartate in the S3‐S4 loop with histidine (D145H) enhanced both the slowing of activation kinetics and the shift in the voltage–conductance curve, such that Zn 2+ inhibition closely resembled that of the human channel. Histidine is much more effective than aspartate in coordinating Zn 2+ in the S3‐S4 linker. A simple Hodgkin Huxley model of NpHV 1 suggests a decrease in the opening rate if it is inhibited by zinc or cadmium. Limiting slope measurements and high‐resolution clear native gel electrophoresis (hrCNE) confirmed that NpHV 1 functions as a dimer. The data support the hypothesis that zinc is coordinated in between the dimer instead of the monomer. Zinc coordination sites may be potential targets for drug development. Abstract : Zinc is bound or coordinated by numerous enzymes. However, the amino acids, involved in zinc coordination, differ between the proteins. Zinc inhibition of the insect voltage‐gated proton channel (NpHV 1) suggests binding at the dimer interface. Zinc competes with protons and is interlocking both monomers in a nonconductive state. The mechanism of inhibition is a nonelectrostatic binding and not a block of the proton permeation pathway through the channel.